Perception of violence and food security in Emohua Local Government Area of Rivers State, Nigeria - Uchendu Jennifer Matthew; Chibuzor Chile Nwobueze; Offor Anthony Onwuzor (Journal of Social, Humanity, and Education, 2023)
Purpose: This study examined perceptions of violence and food security in the Emohua Local Government Area. Research methodology: A descriptive research design was used. The study population was 862,690, of which a sample size of 400 was obtained using Taro Yamane. A self-designed 37 item questionnaire was used to collect data from the respondents. Data were analyzed using descriptive statistics (mean scores and standard deviations). Results: The findings show that loss of life and property, prevalence of stunting growth, underweight and low life expectancy, destruction of farmland, high economic burden on the state economy, malnutrition,  reduction of farming activities and low food production index, effects on both physical and mental health, stunted educational development, psychological trauma, underdevelopment, high risk of diseases, reduction in reproductive rate, increase in prices of foodstuffs, and migration are the relationships between violence conflict and food insecurity. Limitations: Biased while filling the questionnaires and lack of freedom of information in the area. Contribution: There could be no food sufficiency with violent conflict in an area.